Nano-channels in the spider fang for the transport of Zn ions to cross-link His-rich proteins pre-deposited in the cuticle matrix. Issue 1 (January 2017) - Politi, Yael; Pippel, Eckhard; Licuco-Massouh, Ana C.J.; Bertinetti, Luca; Blumtritt, Horst; Barth, Friedrich G.; Fratzl, Peter
Abstract: We identify the presence of multiple vascular channels within the spider fang. These channels seem to serve the transport of zinc to the tip of the fang to cross-link the protein matrix by binding to histidine residues. According to amino acid and elemental analysis of fangs extracted shortly after ecdysis, His-rich proteins are deposited before Zn is incorporated into the cuticle. Microscopic and spectroscopic investigations in the electron microscope and synchrotron radiation experiments suggest that Zn ions are transported through these channels in a liable (yet unidentified) form, and then form stable complexes upon His binding. The resulting cross-linking through the Zn–His complexes is conferring hardness to the fang. Our observations of nano-channels serving the Zn-transport within the His-rich protein matrix of the fibre reinforced spider fang may also support recent bio-inspired attempts to design artificial polymeric vascular materials for self-healing and in-situ curing. Highlights: Histidine–rich proteins are deposited before ecdysis at the tip of the fang. Zn is incorporated into the matrix of the spider fang after ecdysis via an array of nano-channels. Cross-linking of the protein matrix is achieved by zinc ions binding to histidine residues.